From waste pickers to cooperated recyclers: a solidary enterprise case study - Coelho, Diego Bonaldo (2011)
The article intends to analyze and reflect on solidarity enterprises aspects and their social and economic potentials. For its carrying out, it was chosen to interpret the typical solidary enterprise organizing process, regarding its particular characteristics going beyond the economic issue and acquiring important social and political dimensions. A qualitative approach of the phenomenon was used in this research, developed through interpretive nature case study with three data collection strategies adopted: non-participant observations, interviews and document examinations. The case study is on a recycling cooperative formed by waste pickers. The data analysis considered two specific points in the case study: its formation and organizational dynamic. The findings report the case presents insights and interesting gates to reflect on solidary enterprises like organization arrangements, not only including marginalized workers in formality but also influencing social and political aspects of their lives positively, becoming viable public policies mechanisms to local development characterized by inequality reduction and citizenship rescue.